Manufacturing method of all-cotton light and thin anti-ultraviolet fabric and fabric thereof
By performing cation modification treatment and using specific ultraviolet absorbers in the manufacturing process of all cotton thin fabrics, combined with nano titanium dioxide dispersion and adhesives, the UV protection performance problem of the difficulty of cotton fabrics to meet national standards is solved, and high efficiency is achieved Improved UV protection and light resistance.
Patent Information
- Application Number
- CN202411288867.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
Because of its high transmittance to ultraviolet rays, it is difficult to achieve the national standard ultraviolet resistance (UPF>40 and UVA transmittance <5%).
The cationic modification treatment process is added during the manufacturing process, the cotton fiber is modified from anionic to cationic, and two ultraviolet absorbers, diphenyl ethylenediamide and triazine derivatives are combined, and nanotitanium dioxide dispersion is added during the molding. and adhesives for improved UV resistance and wash resistance.
It significantly improves the ultraviolet protection coefficient (UPF value) of the fabric, reduces the UVA transmittance, enhances the light-resistant color fastness and antibacterial effect, and has a small impact on the feel.
Smart Images

Figure CN119194851A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fabrics, and in particular to a method for manufacturing a thin and lightweight all-cotton UV-proof fabric and the fabric. Background Art
[0002] As people's awareness of health and sun protection continues to increase, the demand for sun protection products, especially UV-proof fabrics in textiles, is growing in the market. Ultraviolet rays (UV) can be divided into three types: UVA, UVB and UVC according to their wavelengths. Among them, UVA and UVB can penetrate the atmosphere and cause damage to human skin, such as tanning, sunburn and photoaging, and may even cause skin cancer. Therefore, it is particularly important to develop textiles with high-efficiency UV protection.
[0003] In the field of textile dyeing and finishing, cotton fabrics have always been favored by consumers due to their good breathability and comfort. However, cotton fabrics, especially thin and light-colored fabrics, have a high transmittance to ultraviolet rays, so it is a great technical challenge to achieve the national standard of ultraviolet protection (UPF>40 and UVA transmittance <5%).
[0004] To this end, the present application provides a method for manufacturing a lightweight, ultraviolet-proof all-cotton fabric and the fabric. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present application provides a method for manufacturing a thin and lightweight all-cotton UV-proof fabric and the fabric. The preparation method adds a cationic modification process after pre-treatment and before dyeing treatment to modify the cotton fiber from anionic to cationic, thereby improving the ability of the cotton fiber to bind with the UV absorber. Two types of UV absorbers, diphenyloxalamide and triazine derivatives, are used simultaneously during the dyeing process to improve the UV protection performance. Nano titanium dioxide dispersion and adhesive are added during fabric shaping to enhance the UV protection performance of the fabric and improve the washability.
[0006] The technical solution adopted by this application to solve its technical problem is:
[0007] The first purpose of the present application is to provide a method for manufacturing a pure cotton thin UV-proof fabric, wherein the grey cloth is sequentially subjected to pre-treatment, cationic modification treatment, dyeing treatment, shaping treatment, and pre-shrinkage treatment to obtain the pure cotton thin UV-proof fabric;
[0008] During the dyeing process, an ultraviolet absorber is added to perform an anti-ultraviolet treatment.
[0009] In some specific embodiments, the cationic modification treatment is to use a cationic modifier to modify the pre-treated grey cloth.
[0010] In some specific embodiments, the ultraviolet absorber includes at least one of diphenyloxalamide and triazine derivatives.
[0011] In some specific embodiments, a dispersion is added during the shaping process; the dispersion is a nano-titanium dioxide dispersion.
[0012] In some specific embodiments, the cationic modifier is a quaternary ammonium salt compound.
[0013] In some specific embodiments, the process of the cationic modification treatment is as follows: a modification treatment solution containing 10-50 g / L of a cationic modifier and 1-10 g / L of caustic soda is added to a material tank, and the pre-treated grey cloth is immersed in the modification treatment solution; after the grey cloth is immersed in the material, it enters a stacking box, is heated to 100°C by steam, and is kept in stacking for 20-40 minutes; after the immersion is completed, it is neutralized and washed with water to obtain the modified grey cloth.
[0014] In some specific embodiments, the dye used in the dyeing process includes the following raw materials in percentage by weight:
[0015] Reactive dye 2-10%, UV absorber 3-8%, solvent balance.
[0016] In some specific embodiments, the concentration of the nano-titanium dioxide dispersion used in the shaping treatment is 10-50 g / L.
[0017] In some specific embodiments, during the shaping process, the vehicle speed is 40-60 m / min and the temperature is 130-160°C.
[0018] The second purpose of the present application is to provide fabrics, including fabrics manufactured by the manufacturing method.
[0019] The beneficial effects of this application are:
[0020] 1. The manufacturing method described in the present application adds a cationic modification process after the pre-treatment and before the dyeing treatment to modify the cotton fiber from anionic to cationic, thereby improving the ability of the cotton fiber to bind to the ultraviolet absorber. Two types of ultraviolet absorbers, diphenyloxalamide and triazine derivatives, are used simultaneously during the dyeing process to improve the anti-ultraviolet performance. Nano-titanium dioxide dispersion and adhesive are added during the fabric shaping to enhance the anti-ultraviolet performance of the fabric and improve the washability.
[0021] 2. The manufacturing method described in the present application significantly improves the UPF value (ultraviolet protection factor) of the fabric produced, and significantly reduces the UVA transmittance, which meets the national standards; compared with traditional coating or printing methods, the manufacturing method described in the present application has less impact on the feel of the fabric; through the action of ultraviolet absorbers and nano-titanium dioxide, the damage of ultraviolet rays to dyes and fibers is reduced, the light fastness of the fabric is improved, and nano-titanium dioxide produces strongly oxidizing hydroxyl free radicals or superoxide ions under the action of light, so that the fabric has an antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0023] Figure 1 This is a process flow chart of the manufacturing method of the all-cotton thin ultraviolet protection fabric described in this application. DETAILED DESCRIPTION
[0024] The following will clearly and completely describe the concept, specific structure and technical effects of the present application in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present application. In addition, all the connection / connection relationships involved in the patent do not simply refer to the direct connection of components, but refer to the formation of a better connection structure by adding or reducing connection accessories according to the specific implementation situation. The various technical features created in this application can be combined interactively without conflicting with each other.
[0025] Explanation of terms
[0026] Grey cloth refers to cloth that has not been printed or dyed, also known as natural cloth. It is a semi-finished product in the textile industry, usually made of natural fibers such as cotton, wool, linen, silk, or chemical fibers through spinning, weaving, and other processes. In this application, grey cloth is the starting material in the manufacturing process of all-cotton light and thin UV-proof fabrics, such as 80S woven plain dyed cloth.
[0027] Pad dyeing is a continuous dyeing process that uses a padder to roll the dye liquor evenly into the fabric, and then undergoes a color fixing treatment such as steaming or drying to firmly combine the dye with the fiber. In the manufacture of all-cotton light and thin UV-proof fabrics, the pad dyeing process is used to evenly penetrate the reactive dye and UV absorber into the fabric to achieve dyeing and UV-proof treatment of the fabric.
[0028] A method for manufacturing a pure cotton thin ultraviolet-proof fabric, comprising sequentially subjecting the grey fabric to pretreatment, cationic modification, dyeing, shaping and preshrinking to obtain the pure cotton thin ultraviolet-proof fabric;
[0029] During the dyeing process, an ultraviolet absorber is added to perform an anti-ultraviolet treatment.
[0030] In some specific embodiments, the specific process of the pre-treatment is to perform singeing, cold batch desizing, scouring in a scouring and bleaching machine, and bleaching on the grey cloth in sequence;
[0031] Specifically, singeing is to quickly burn the surface of the grey fabric with a high-temperature flame or electric heating plate to remove the fluff and fine fibers on the surface. During the singeing process, the high temperature is used to instantly carbonize and fall off the fluff on the surface of the fabric, improving the surface finish of the fabric and preventing the presence of fluff from affecting product quality in subsequent processing.
[0032] Specifically, cold stack desizing is to immerse the grey cloth in a solution containing a desizing agent, stack it for a period of time, allow the sizing agent to swell and dissolve, and then remove it by washing. The swelling and dissolving effect of the desizing agent on the sizing agent destroys the binding force between the sizing agent and the fiber, causing the sizing agent to fall off the fiber, thereby improving the wettability and softness of the fabric.
[0033] Specifically, the scouring and bleaching machine scours and bleaches. The desized grey cloth is sent to the scouring and bleaching machine for scouring under high temperature and alkaline conditions to remove natural impurities and residual slurry in the fiber, and then bleaching is added to improve the whiteness and purity of the fabric. During the scouring process, the alkaline conditions cause the natural impurities and residual slurry to hydrolyze and dissolve, and the bleaching agent destroys the chromophore of the pigment, making the fabric white.
[0034] Therefore, in the pre-treatment process, the grey cloth is subjected to steps such as singeing, cold-batch desizing, scouring and bleaching to gradually remove the fluff, fine fibers, natural impurities and residual slurry on the surface of the fabric, improve the wettability and whiteness of the fabric, and provide a good foundation for subsequent cationic modification, dyeing and shaping processes.
[0035] In some specific embodiments, the specific process of the cationic modification treatment includes the following steps:
[0036] Treatment preparation: In the material tank, prepare to add cationic modifier (trade name Quat-188, Dow Chemical) and caustic soda.
[0037] Solution preparation: dissolve the cationic modifier and caustic soda in water to prepare a modified treatment solution (wherein the concentration of the cationic modifier is 10-50 g / L, and the concentration of the caustic soda is 1-10 g / L).
[0038] Fabric padding: The grey fabric after scalding and bleaching is dipped into the modification treatment solution to ensure that the grey fabric fully absorbs the modification treatment solution.
[0039] Stacking reaction: After the grey cloth is impregnated, it enters the stacking box, where it is heated to 100°C by steam and kept stacked for 20-40 minutes to allow the cationic modifier to fully react with the cotton fiber.
[0040] Neutralization and washing: After stacking, the fabric enters the washing box for neutralization and washing. The pH value is adjusted between 6-8 with acetic acid to remove excess alkali and unreacted cationic modifiers.
[0041] During the production process, the cotton fibers of the grey cloth are anionic in nature, and the UV absorbers are also mostly anionic. Therefore, under normal circumstances, there is electrostatic repulsion between the UV absorbers and the cotton fibers, making it difficult to effectively combine them. In the cationic modification treatment, the cotton fibers are modified from anionic to cationic through cationic modification, thereby improving their affinity with the UV absorbers.
[0042] In the present application, a cationic modifier (such as Quat-188 or other quaternary ammonium salt compounds) reacts with cotton fibers under alkaline conditions, and changes the charge properties of the cotton fiber surface to cationic properties through chemical bonds or physical adsorption. This modification process enhances the cotton fiber's ability to absorb the subsequently added ultraviolet absorber.
[0043] At the same time, after cationic modification, cotton fibers can more effectively combine with UV absorbers (such as diphenyloxalamide and triazine derivatives) during the subsequent dyeing process, increasing the adhesion and stability of UV absorbers on cotton fibers, thereby significantly improving the UV protection performance of the fabric.
[0044] Therefore, cationic modification treatment is carried out to change the charge properties of cotton fibers, thereby enhancing their affinity for UV absorbers and thus improving the UV protection performance of the fabric.
[0045] In some specific embodiments, the specific process of the dyeing treatment includes the following steps:
[0046] (1) Prepare dye solution:
[0047] Reactive dyes (such as reactive blue SF, reactive yellow 3RF, reactive red 3BF, etc.) and ultraviolet absorbers (such as diphenyloxalamide type ultraviolet absorbers UV-SUN CEL.LIQ and triazine derivative type ultraviolet absorbers TANUVAL CPA) are mixed in a certain proportion to prepare a dyeing solution. The specific proportion is determined according to the required color and ultraviolet protection effect.
[0048] More specifically, the UV absorber is added to combine with the cationic modified cotton fibers during the dyeing process to improve the UV protection of the fabric.
[0049] (2) Dyeing operation:
[0050] The mercerized fabric is dyed on a continuous pad dyeing machine.
[0051] The process includes: padding dye solution → hot air pre-drying → drum drying → over-stacking → padding salt and alkali solution → steam fixation → cold water washing → hot water washing → soap washing.
[0052] The vehicle speed is controlled at 45-50 m / min and the rolling rate is 55%-65% to ensure that the dye and UV absorber penetrate into the fabric evenly.
[0053] In the present application, the reactive dye reacts with the hydroxyl groups on the cotton fiber under alkaline conditions to form a covalent bond, so that the dye is firmly fixed on the cotton fiber;
[0054] During the dyeing process, ultraviolet absorbers (such as diphenyloxalamide and triazine derivatives) are attracted to the cationic-modified cotton fibers and bonded to the cotton fibers through physical or chemical effects, thereby improving the UV protection of the fabric.
[0055] More specifically, diphenyloxalamide and triazine derivatives, as UV absorbers, can absorb UV rays and convert them into heat or other forms of energy, thereby preventing UV rays from damaging the skin; the simultaneous use of diphenyloxalamide and triazine derivatives can achieve higher UV protection performance than a single UV absorber.
[0056] In summary, dyeing is one of the key steps in the manufacturing process of all-cotton lightweight UV-proof fabrics. Through a reasonable ratio of dyes and UV absorbers and precise dyeing process control, it can be ensured that the fabric has excellent UV protection while obtaining good color.
[0057] In some specific embodiments, the specific process of the shaping treatment includes the following steps:
[0058] (1) Preparation stage:
[0059] The nano titanium dioxide powder is added into the ethanol solution, and the solution is dispersed under 200-400W ultrasonic vibration for 5-20 minutes to prepare an anionic nano titanium dioxide dispersion.
[0060] Prepare the auxiliary chemicals such as softeners, penetrants, adhesives, etc. required for shaping, and mix them according to a certain concentration.
[0061] (2) Equipment preparation:
[0062] Use the setting machine to perform stenting and setting operations to ensure that the equipment is in good working condition and that parameters such as temperature and speed can be adjusted to the required range.
[0063] (3) Application of chemicals:
[0064] The dyed fabric is softened on the setting machine, and the prepared nano titanium dioxide dispersion and adhesive are added. These chemicals are evenly distributed on the fabric to ensure that the nano titanium dioxide can fully contact and adsorb with the cationic modified cotton fiber.
[0065] (4) Tentering and shaping:
[0066] Set the speed of the setting machine to 40-60m / min and the temperature to 130-160℃. According to the specific characteristics of the fabric, these parameters can be adjusted to achieve the best effect.
[0067] Nano titanium dioxide dispersion and adhesive are added when the fabric is finalized. Nano titanium dioxide has the function of shielding ultraviolet rays, but because it is in the form of small solid particles, it has no affinity for cotton fibers and is generally applied to the fabric by coating or printing. In the present application, a nano titanium dioxide dispersion is first prepared. Since the dispersion is anionic, it can be adsorbed with cationic modified cotton fibers. Then, under the action of an adhesive (acrylic adhesive or ACRAMINALW-T adhesive of Tuona Chemical), it is more firmly combined with the fabric, making it have better wash resistance. The nano titanium dioxide dispersion has little effect on the feel, which solves the problem that the coating printing method has a greater impact on the feel.
[0068] Moreover, due to the absorption and reflection of light by two types of ultraviolet absorbers, diphenyloxalamide and triazine derivatives, and nano-titanium dioxide, the influence of high energy of ultraviolet rays on dye chromophores and fabric fibers is reduced, thereby improving the light fastness of fabrics. In addition, nano-titanium dioxide generates electron-hole pairs under the action of light, which react with water or oxygen to generate highly oxidizing hydroxyl free radicals or superoxide ions, which can destroy bacterial cell membranes and make bacteria inactive, thereby making fabrics also have antibacterial effects.
[0069] In the present application, the adhesive added during the shaping process can further enhance the bonding force between nano-titanium dioxide and cotton fibers, and improve the washability and durability of the UV protection layer. The adhesive can chemically react or physically cross-link with the cotton fibers and nano-titanium dioxide at high temperatures to form a stable combination.
[0070] In this application, by controlling the speed, temperature and tension of the setting machine, the setting process can be optimized to ensure that the nano-titanium dioxide dispersion and adhesive are evenly distributed on the fabric and fully react. The setting process can also be adjusted according to the specific characteristics and needs of the fabric to achieve the best UV protection effect and feel.
[0071] In some specific implementations, the specific process of the pre-shrinkage treatment includes the following steps:
[0072] The dyed and shaped fabric is sent to the shrinking machine. The shrinking machine is started, and the rubber blanket starts to run, driving the fabric to move on it. During the movement, the shrinking effect of the rubber blanket will cause the fabric to shrink to a certain extent in the warp direction, thereby controlling its shrinkage rate. By adjusting the parameters of the shrinking machine (such as the tension of the rubber blanket, the running speed, etc.), the shrinkage degree of the fabric can be controlled to achieve the desired shrinkage rate control target. The shrinkage of the fabric is driven by the rubber blanket of the shrinking machine to control the shrinkage of the fabric in the warp direction (generally controlled within -3% to 0);
[0073] In this application, the pre-shrinking treatment uses physical and mechanical methods to shrink the fabric to a certain extent, so as to simulate the dimensional changes that may occur during subsequent use, and fix its new dimensional state in this process. When the fabric is subjected to external forces again in subsequent use, its dimensional changes will be limited to a certain extent, thereby improving dimensional stability.
[0074] The following examples are used to further illustrate the method for manufacturing the all-cotton, lightweight, UV-proof fabric described in the present application.
[0075] Example 1
[0076] Taking 80S woven plain dyed cloth as an example, a pure cotton light and thin anti-ultraviolet fabric is prepared. The manufacturing method of the pure cotton light and thin anti-ultraviolet fabric comprises the following steps:
[0077] S1. Pre-treatment
[0078] Grey cloth is singed, cold-batch desizing, scouring and bleaching in the bleaching machine in sequence;
[0079] S2. Cationic modification
[0080] Add cationic modifier and caustic soda into the material tank behind the scouring and bleaching machine to prepare a modified treatment solution; the concentration of the cationic modifier in the modified treatment solution is 50g / L, and the concentration of caustic soda is 10g / L, and the grey cloth is dipped in the modified treatment solution;
[0081] After the grey cloth is dipped in the liquid, it enters the stacking box, where it is heated to 100°C by steam, stacked for 40 minutes, and then enters the washing box for neutralization and water washing, and the pH is adjusted to between 6 and 8 by acetic acid;
[0082] S3. Staining
[0083] The washed grey cloth is dyed with reactive dyes on a continuous pad dyeing machine. The specific process is as follows:
[0084] Pad dye solution → hot air pre-drying → drum drying → over-stacking → padding salt and alkali solution → steam fixation → cold water washing → hot water washing → soap washing;
[0085] Continuous pad dyeing machine, speed 50m / min, padding rate 65%;
[0086] The dye liquor includes the following raw materials by weight:
[0087] Reactive Blue SF: 1.5%;
[0088] Reactive Yellow 3RF: 0.5%;
[0089] Reactive Red 3BF: 1.2%;
[0090] Diphenyloxalamide UV absorber UV-SUN CEL.LIQ (Archroma Chemicals): 5%;
[0091] Triazine derivative UV absorber TANUVAL CPA (Tonano Chemical): 3%;
[0092] Water balance.
[0093] S4. Finalization
[0094] The dyed fabric is softened on a setting machine, and the prepared nano titanium dioxide dispersion and adhesive are added for tentering and setting. The process is as follows:
[0095] Softener (ULTRATEX FMW from Archroma Chemicals): 40g / L
[0096] Penetrant (FORYL WET from Kekai Chemical): 3g / L
[0097] Nano titanium dioxide dispersion: 50g / L
[0098] Adhesive (ACRAMIN ALW-T from Tona Chemicals): 10g / L
[0099] Fabric feeding from the front, speed 60m / min, temperature 160℃;
[0100] The preparation method of nano titanium dioxide dispersion is as follows:
[0101] The nano-titanium dioxide powder is added into the ethanol solution, and the solution is dispersed under 200W ultrasonic vibration for 20 minutes to obtain the nano-titanium dioxide dispersion.
[0102] S5. Pre-shrink
[0103] The rubber blanket of the preshrinking machine drives the fabric to shrink and controls the shrinkage in the warp direction of the fabric.
[0104] Example 2
[0105] The manufacturing method of the all-cotton light and thin UV-proof fabric comprises the following steps:
[0106] In step S2, the concentration of the cationic modifier in the modification treatment solution is 10 g / L, and the concentration of caustic soda is 1 g / L, and the grey cloth is dipped in the modification treatment solution;
[0107] After the grey cloth is dipped in the liquid, it enters the stacking box, where it is heated to 100°C by steam and stacked for 20 minutes.
[0108] In step S3, the continuous padding machine has a speed of 45 m / min and a padding rate of 55%;
[0109] A dye liquor comprising the following raw materials in amounts by weight:
[0110] Reactive Blue SF: 1.5%;
[0111] Reactive Yellow 3RF: 0.5%;
[0112] Reactive Red 3BF: 1.2%;
[0113] Diphenyloxalamide UV absorber UV-SUN CEL.LIQ (Archroma Chemicals): 3%-5%;
[0114] Triazine derivative UV absorber TANUVAL CPA (Tonano Chemical): 1%-3%;
[0115] Water balance.
[0116] In step S4, softener (ULTRATEX FMW from Archroma Chemicals): 10 g / L, penetrant (FORYLWET from Kekai Chemicals): 1 g / L, nano titanium dioxide dispersion: 10 g / L, adhesive (ACRAMIN ALW-T from Tona Chemicals): 2 g / L; fabric feeding from the front, speed 40 m / min, temperature 130°C;
[0117] The remaining conditions are the same as those in Example 1.
[0118] Example 3
[0119] The manufacturing method of the all-cotton light and thin UV-proof fabric comprises the following steps:
[0120] In step S2, the concentration of the cationic modifier in the modification treatment solution is 35 g / L, and the concentration of caustic soda is 7 g / L, and the grey cloth is dipped in the modification treatment solution;
[0121] After the grey cloth is dipped in the liquid, it enters the stacking box, where it is heated to 100°C by steam and stacked for 35 minutes.
[0122] In step S3, the continuous padding machine has a speed of 48 m / min and a padding rate of 60%;
[0123] A dye liquor comprising the following raw materials in amounts by weight:
[0124] Reactive Blue SF: 1.5%;
[0125] Reactive Yellow 3RF: 0.5%;
[0126] Reactive Red 3BF: 1.2%;
[0127] Diphenyloxalamide UV absorber UV-SUN CEL.LIQ (Archroma Chemicals): 4%;
[0128] Triazine derivative UV absorber TANUVAL CPA (Tonano Chemical): 2.5%;
[0129] Water balance.
[0130] In step S4, softener (ULTRATEX FMW from Archroma Chemicals): 30 g / L, penetrant (FORYLWET from Kekai Chemicals): 2 g / L, nano titanium dioxide dispersion: 40 g / L, adhesive (ACRAMIN ALW-T from Tona Chemicals): 7 g / L; fabric feeding from the front, speed 40-60 m / min, temperature 150°C;
[0131] The remaining conditions are the same as those in Example 1.
[0132] Example 4
[0133] The manufacturing method of the all-cotton light and thin UV-proof fabric comprises the following steps:
[0134] In step S2, the concentration of the cationic modifier in the modification treatment solution is 15 g / L, and the concentration of caustic soda is 2 g / L, and the grey cloth is dipped in the modification treatment solution;
[0135] After the grey cloth is dipped in the liquid, it enters the stacking box, where it is heated to 100°C by steam and stacked for 25 minutes.
[0136] In step S3, the continuous padding machine has a speed of 47 m / min and a padding rate of 57%;
[0137] A dye liquor comprising the following raw materials in amounts by weight:
[0138] Reactive Blue SF: 1.5%;
[0139] Reactive Yellow 3RF: 0.5%;
[0140] Reactive Red 3BF: 1.2%;
[0141] Diphenyloxalamide UV absorber UV-SUN CEL.LIQ (Archroma Chemicals): 3.5%;
[0142] Triazine derivative UV absorber TANUVAL CPA (Tonano Chemical): 1.5%;
[0143] Water balance.
[0144] In step S4, softener (ULTRATEX FMW from Archroma Chemicals): 15 g / L, penetrant (FORYLWET from Kekai Chemicals): 1.5 g / L, nano titanium dioxide dispersion: 20 g / L, adhesive (ACRAMIN ALW-T from Tona Chemicals): 3 g / L; fabric feeding from the front, speed 45 m / min, temperature 140°C;
[0145] The remaining conditions are the same as those in Example 1.
[0146] Comparative Example 1
[0147] The manufacturing method of the all-cotton light and thin UV-proof fabric comprises the following steps:
[0148] In step S2, no modification treatment liquid is added.
[0149] Comparative Example 2
[0150] The manufacturing method of the all-cotton light and thin UV-proof fabric comprises the following steps:
[0151] In step S2, no adhesive is added.
[0152] The fabrics prepared in Examples 1-4 and Comparative Examples 1-2 were tested for UV protection, light fastness, and antibacterial properties. The specific test items are shown in Table 1 below:
[0153] Table 1
[0154]
[0155] The test results are summarized in Table 2 below;
[0156] Table 2
[0157]
[0158] From the test results in Table 2, it can be seen that in Examples 1 to 4, the UPF values of the fabrics obtained by the manufacturing method of the present application before and after washing 30 times are much higher than 40, and the T(UVA)AV values are all lower than 5%, which meets the anti-ultraviolet performance requirements of the national standard.
[0159] Comparative Example 1 did not use a cationic modifier, and the fabric prepared had a low UPF value before and after 30 washes, and a high T (UVA) AV value, which did not meet the national standards.
[0160] In Comparative Example 2, no adhesive was used, and the UPF value of the fabric prepared was lower than that of Example 1 before and after washing 30 times, and the T(UVA)AV value was higher than that of Example 1.
[0161] The color fastness to light of the fabrics of Examples 1 to 4 is all level 5, indicating that these fabrics have excellent color fastness to light. The color fastness to light of the fabrics of Comparative Examples 1 and 2 is level 4, indicating that the color fastness to light of the fabrics without using the cationic modifier or the fabrics using the adhesive is poor.
[0162] After washing 100 times, the fabrics of Examples 1 to 4 showed high antibacterial rates against Staphylococcus aureus, Escherichia coli and Candida albicans, which were above 90%, above 80% and above 70% respectively. In Comparative Example 1, the antibacterial performance decreased to a certain extent; while the antibacterial performance of the fabric of Comparative Example 2 decreased significantly, especially the antibacterial performance against Candida albicans decreased to 57%, indicating that the antibacterial performance of the fabric without adhesive was poor.
[0163] The above is a specific description of the preferred implementation of the present application, but the invention of the present application is not limited to the described embodiments. Technical personnel familiar with the field can also make various equivalent modifications or substitutions without violating the spirit of the present application. These equivalent modifications or substitutions are all included in the scope defined by the claims of the present application.
Claims
1. A method for manufacturing a thin and lightweight all-cotton UV-proof fabric, characterized in that: The grey cloth is sequentially subjected to pre-treatment, cationic modification treatment, dyeing treatment, shaping treatment, and pre-shrinking treatment to obtain the all-cotton light and thin UV-proof fabric; During the dyeing process, an ultraviolet absorber is added to perform an anti-ultraviolet treatment.
2. The manufacturing method according to claim 1, characterized in that: The cationic modification treatment is to use a cationic modifier to modify the pre-treated grey cloth.
3. The manufacturing method according to claim 1, characterized in that: The ultraviolet absorber includes at least one of diphenyloxalamide and triazine derivatives.
4. The manufacturing method according to claim 1, characterized in that: During the shaping process, a dispersion is added; the dispersion is a nano titanium dioxide dispersion.
5. The manufacturing method according to claim 2, characterized in that: The cationic modifier is a quaternary ammonium salt compound.
6. The manufacturing method according to claim 1, characterized in that: The process of the cationic modification treatment is as follows: adding a modification treatment liquid containing 10-50g / L of a cationic modifier and 1-10g / L of caustic soda into a material tank, and immersing the pre-treated grey cloth in the modification treatment liquid; after immersion and immersion, the grey cloth enters a stacking box, is heated to 100°C by steam, and is kept stacked for 20-40 minutes; after immersion and immersion, neutralization and water washing are performed to obtain the modified grey cloth.
7. The manufacturing method according to claim 1, characterized in that: The dye used in the dyeing process comprises the following raw materials in percentage by weight: Reactive dye 2-10%, UV absorber 3-8%, solvent balance.
8. The manufacturing method according to claim 1, characterized in that: The concentration of the nano-titanium dioxide dispersion used in the shaping treatment is 10-50 g / L.
9. The manufacturing method according to claim 1, characterized in that: During the shaping process, the vehicle speed is 40-60 m / min and the temperature is 130-160°C.
10. Fabric, characterized in that, The invention relates to a fabric produced by the production method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for finishing durable function of cellulose fabric
CN101709549A
Antibacterial, waterproof and sunlight-resisting dacron decoration fabric
CN103498330A
Finishing method for one-bath process cationic modified reactive dyeing
CN108486930A
Fabric finishing liquid with anti-ultraviolet function and anti-ultraviolet function cotton fabric prepared through fabric finishing liquid
CN110029495A
Preparation method of antibacterial and ultraviolet-proof multifunctional rayon dyed knitted fabric
CN112877879A
